A Thermo-Active Laccase Isoenzyme From Trametes trogii and Its Potential for Dye Decolorization at High Temperature - Yang, Xulei (Front Microbiol, 2020)
A thermo-activation and thermostable laccase isoenzyme (Lac 37 II) produced by Trametes trogii S0301 at 37°C was purified to apparent homogeneity by anionic exchange chromatography and sephadex G-75 chromatography, with 12.3% of yeiled and a specific activity of 343.1 U mg(–1). The molecular weight of the purified Lac 37 II was estimated to be approximately 56 kDa in 12% sodium dodecyl sulfate polyacrylamide gel electrophoresis (SDS-PAGE). The optimal pH and temperature for the protein was 2.7 and 60°C, respectively. The purified Lac 37 II showed higher resistance to all tested metal ions and organic solvents except for Fe(2+) and Cd(2+) at 37°C and the activity of the purified Lac 37 was significantly enhanced by Cu(2+) at 50 mM. The K(cat), K(m), and K(cat)/K(m) of Lac 37 II were 2.977 s(–1), 16.1 μM, and 184.9 s(–1) μM(–1), respecively, in the condition of pH 2.7 and 60°C using ABTS as a substrate. Peptide-mass fingerprinting analysis showed that the Lac 37 II matched to the gene-deduced sequences of lcc3 in T. trogii BAFC 463, other than Lcc1, Lcc 2, and Lcc 4. Compared with laccase prepared at 28°C, the onset of thermo-activation of Lac 37 II activity occurred at 30°C with an increase of 10%, and reached its maximum at the temperatures range of 40–60°C with an increase of about 40% of their original activity. Furthermore, Lac 37 II showed the efficient decolorization ability toward triphenylmethane dyes at 60°C, with decolorization rates of 100 and 99.1% for 25 mg L(–1) malachite and crystal violet in 5 h, respectively, when hydroxybenzotriazole (HBT) was used as a mediator. In conclusion, it is the first time to report a thermo-activation laccase from a thermophilic T. trogii strain, which has a better enzyme property and higher decolorization ability among fungal laccases, and it also has a further application prospective in the field of biotechnology.